2014
DOI: 10.1177/0284185114561915
|View full text |Cite
|
Sign up to set email alerts
|

The value of ADC, T2 signal intensity, and a combination of both parameters to assess Gleason score and primary Gleason grades in patients with known prostate cancer

Abstract: Background: The ability to non-invasively analyze tumor aggressiveness is an important predictor for individual treatment stratification and patient outcome in prostate cancer (PCA). Purpose: To evaluate: (i) whether apparent diffusion coefficient (ADC), the T2 signal intensity (SI), and a combination of both parameters allow for an improved discrimination of Gleason Score (GS) !7 (intermediate and high risk) and GS <7 (low risk) in PCA; and (ii) whether ADC may distinguish between 3 þ 4 and 4 þ 3 PCA (primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…The role of ADC metrics in differentiating GP 3+4 vs 4+3 PCa have been addressed by few studies [19,20,28]. A study on 57 GS=7 PCa showed that ADC/T2 ratio, defined as the ratio of ADC values and of the signal intensity of the tumor measured respectively on ADC maps and T2WI, had a sensitivity of 77.5% and a specificity of 64.7% in discriminating GP 3+4 from 4+3 PCa [29].…”
Section: Discussionmentioning
confidence: 99%
“…The role of ADC metrics in differentiating GP 3+4 vs 4+3 PCa have been addressed by few studies [19,20,28]. A study on 57 GS=7 PCa showed that ADC/T2 ratio, defined as the ratio of ADC values and of the signal intensity of the tumor measured respectively on ADC maps and T2WI, had a sensitivity of 77.5% and a specificity of 64.7% in discriminating GP 3+4 from 4+3 PCa [29].…”
Section: Discussionmentioning
confidence: 99%
“…T2 values of histologically proven malignant tumor areas were significantly lower than the suspicious lesions but nonmalignant lesions or normal areas [26]. The use of quantitative T2 measurement improves the specificity and/or sensitivity of prostate cancer detection [27] and aggressiveness assessment [28, 29]. There is a potential benefit of incorporating quantitative T2 values into CADx systems.…”
Section: Mr Image Acquisitionsmentioning
confidence: 99%
“…The Gleason grading system is a fundamental indicator of the aggressive nature of prostate cancer. Studies found that ADC image features correlate with Gleason scores [27, 28, 46, 154156]. A study by Yamamura et al found a highly significant negative correlation between ADC-value and the Gleason score, while MRS did not show a significant correlation [157].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…1 Today, mpMRI plays a pivotal role in the diagnosis and risk stratification of men with prostate cancer. 3,4 T 2 -WI generates a high signal-to-noise ratio (SNR) and confers high spatial resolution. 3,4 T 2 -WI generates a high signal-to-noise ratio (SNR) and confers high spatial resolution.…”
mentioning
confidence: 99%